The Implementation of Digital Media in English Teaching at SMA IT Dasan Baru - Khaerunnisa (INOVASI, 2025)
This research aims to explore the implementation of digital media in English teaching at SMA IT Dasan Baru. Through a qualitative descriptive approach, the research involved interviews with teachers and students, as well as classroom observations. The study intends to identify the benefits of digital media in improving language skills such as speaking, listening, reading, and writing, while also considering the challenges faced in a pesantren environment. The findings of this study are expected to benefit both theoretical and practical perspectives, offering a deeper understanding of how digital media can be leveraged to support English learning in traditional school settings, and motivating students to engage more effectively in language acquisition.